Cover Feature: Theoretical Insights into Bifurcated Intramolecular Dihydrogen Bonds (ChemPhysChem 4/2024) - Gholami, Samira; Aarabi, Mohammad; Grabowski, Sławomir J. (Chemphyschem, 2024)
The Cover Feature presents three conformers of (1Z,4Z)‐1,4‐dipentene‐3‐bora‐1,5‐diol corresponding to local energetic minima. The most energetically stable is the conformer with two intramolecular dihydrogen bonds, DHBs, that possess the same hydride Lewis base centre (bifurcated dihydrogen bond). The opening of one of the intramolecular dihydrogen bonded rings leads to the conformer of the higher energy with the single DHB. The conformer without DHBs is characterised by the highest energy. More information can be found in the Research Article by Samira Gholami, Mohammad Aarabi, and Sławomir J. Grabowski .